Repercussions of the work organization in the health and the quality of life of the coordinators of the nursing. A qualitative study - Luiza Mara Correia; Norma Valéria Dantas de Oliveira Souza; Maria Ivone Chaves Mauro; Raquel Matoso da Silva (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
Historical-social study with qualitative approach, whose object dealt with the characteristics of the organization of the work and its repercussion in the health and the life of the coordinators of the Nursing school of University of the State of Rio De Janeiro (FENF/UERJ) in 1982-1999. It had as objective: to characterize the work organization of the coordinators of the Boarding school of Nursing and to discuss the repercussions of the work organization in the health and the quality of life of these coordinators. The collection scenes were the coordination of graduation from FENF/UERJ's places of work. The data were collected through interview and documentary analysis in the months of June and July of 2005. The results of the analysis disclosed that the characteristics of the labor organization are: authoritarianism, inflexibility, strong relations of power; complexity and intense labor rhythm. It was verified that these characteristics had a negative repercussion in the health and the quality of life of the coordinators.